Data for: "Causal models of rate-independent damping in insect exoskeleta" - Pons, Arion (Chalmers University of Technology, 2025)
Code in MATLAB r2022b, containing relevant data, for the journal article: Pons, "Causal models of rate-independent damping in insect exoskeleta", Journal of Experimental Biology, 2025. Code is annotated, and includes fitting analysis and and numerical methods for damping models.

Kod i MATLAB r2022b, innehållande relevant data, för tidskriftsartikeln: Pons, "Causal models of rate-independent damping in insect exoskeleta", Journal of Experimental Biology, 2025. Koden är kommenterad, och inkluderar passningsanalys och numeriska metoder för dämpningsmodeller.
Data om: "Causal models of rate-independent damping in insect exoskeleta"
Keywords: biomechanics; insects; Drosophila melanogaster; blaberus discoidalis serville, 1838; manduca sexta linnaeus, 1763; insect exoskeleton; insektens exoskelett; Computational Mathematics; Beräkningsmatematik; Zoology; Zoologi; Applied Mechanics; Teknisk mekanik